Well-Being In Breastfeeding Mother - Reina Dhamanik; Anggorowati Anggorowati; Sari Sudarmiati (Universitas Muhammadiyah Semarang, 2020)
Well-being is something that everyone, especially breastfeeding mothers, wants to achieve. Well-being is needed by postpartum mothers to play a new role optimally in the lactation process. The individual experience of breastfeeding is influenced by knowledge, positive affect and a lot of confidence in the breastfeeding process to achieve well-being during the postpartum psychological adaptation process. This study aims to describe the well-being of breastfeeding mothers. Literature review regarding the well-being of breastfeeding mothers using databases from ProQuest, ScienceDirect, JSTOR, and Scopus obtained from 2008-2020 with a total of 10 articles. Synthesis analysis reveals seven aspects that affect the well-being of postpartum mothers in the breastfeeding process, such as 1) family support, 2) self-efficacy, 3) initiation in the first time breastfeeding. 4) positive mood, 5) awareness of self-acceptance, 6) negative obstetric experience, 7) knowledge. Postpartum mothers can improve well-being through the management of factors that influence postpartum psychological adaptation as a positive preventive effort in increasing the ability of the lactation process to prevent ineffective breastfeeding.